Urban compared with rural and remote burn hospitalisations in Western Australia - Duke, Janine; Rea, S.; Semmens, James; Wood, Fiona (Elsevier, 2011)
Aim: To compare the incidence, temporal trends and cause of burn hospitalisations between urban, rural and remote regions in Western Australia, 1983–2008. Methods: De-identified linked hospital morbidity and mortality records for all persons hospitalised for an index burn in Western Australia were analysed 1983–2008. Annual age-specific incidence and age standardised rates were estimated. Poisson regression analyses were used to estimate temporal trends in hospital admissions by urban, rural and remote region. Results: Of 23,450 burn-related hospital admissions 1983–2008, 14,007 (59.7%) were in urban, 5442 (23.1%) rural and 4021 (17.2%) remote hospital regions. Hospitalisation rates were higher in rural (Incidence rate ratio (IRR), 95% CI: 1.5, 1.4–1.6) and remote (IRR, 95%C: 2.1, 2.0–2.2) regions compared to urban. Age-standardised rates of burn hospital admissions declined from 1983 to 2008 for each region with 26-year declines of 56% (95% CI: 51–60) for remote, 71% (95% CI: 68–73) for rural, and 9% (95% CI: 4–14) for admissions in urban regions. Scald was the most common cause for urban admissions while flame the most common cause for rural and remote burn admissions. Conclusions: Significant differences in the incidence, and cause of burn were identified between urban, rural and remote regions in Western Australia.